Environmental Health and Safety Hazards of Indigenous Small-Scale Gold Mining Using Cyanidation in the Philippines - Ana Marie R. Leung; Jinky Leilanie DP. Lu (SAGE Publishing, 2016)
Objectives This cross-sectional study aimed at the environmental health hazards at work and cyanide exposure of small-scale gold miners engaged in gold extraction from ores in a mining area in the Philippines. Methods Methods consisted of structured questionnaire-guided interviews, work process observation tools, physical health assessment by medical doctors, and laboratory examination and blood cyanide determination in the blood samples of 34 indigenous small-scale gold miners from Benguet, Philippines. Results The small-scale gold miners worked for a mean of 10.3 years, had a mean age of 36 years, with mean lifetime mining work hours of 18,564. All were involved in tunneling work (100%) while a considerable number were involved in mixing cyanide with the ore (44%). A considerable number were injured (35%) during the mining activity, and an alarming number (35%) had elevated blood cyanide level. The most prevalent hazard was exposure to chemicals, particularly to cyanide and nitric acid, which were usually handled with bare hands. Conclusion The small-scale gold miners were exposed to occupational and environmental hazards at work.